Small Airways: The “Silent Zone” of 2021 GINA Report? - Cottini, Marcello; Lombardi, Carlo; Passalacqua, Giovanni; Bagnasco, Diego; Berti, Alvise; Comberiati, Pasquale; Imeri, Gianluca; Landi, Massimo; Heffler, Enrico (Frontiers in Medicine, 2022)
Asthma is a chronic disease, affecting approximately 350 million people worldwide. Inflammation and remodeling in asthma involve the large airways, and it is now widely accepted that the small airways (those with an internal diameter <2 mm) are involved in the pathogenesis of asthma and are the major determinant of airflow obstruction in this disease. From a clinical perspective, small airways dysfunction (SAD) is associated with more severe bronchial hyperresponsiveness, worse asthma control and more exacerbations. Unlike the GOLD guidelines which, in their definition, identify COPD as a disease of the small airways, the Global Initiative for Asthma (GINA) guidelines do not refer to the prevalence and role of SAD in asthmatic patients. This decision seems surprising, given the growing body of compelling evidence accumulating pointing out the high prevalence of SAD in asthmatic patients and the importance of SAD in poor asthma control. Furthermore, and remarkably, SAD appears to possess the characteristics of a treatable pulmonary trait, making it certainly appealing for asthma control optimization and exacerbation rate reduction. In this mini-review article, we address the most recent evidence on the role of SAD on asthma control and critically review the possible inclusion of SAD among treatable pulmonary traits in international guidelines on asthma.